Achalasia Treatment: From the Whale Bone to POEM. Issue 4 (December 2022) - Schlottmann, Francisco; Herbella, Fernando A. M.; Patti, Marco G.
Achalasia treatment started with forceful dilatation of the cardia with the aid of whale bones in the 17th century. In the following 3 centuries, treatment alternated between endoscopic and surgical therapy with advances in both fields. Surgery evolved from cardioplasties to cardiomytomy, from open approach to minimally invasive, from the thoracic route to the abdomen, from human hands to robotic arms. Endoscopic therapy evolved from dilatation with whale bones to pneumatic balloons, from botulinum toxin injection to peroral endoscopic myotomy.